Respuesta :

Answer: Recursive  formula of the given geometric sequence is [tex]a_{n}=a_{1}r^{n-1}[/tex].

Step-by-step explanation:

All geometric sequences have a first term  a  and common ratio r .

Now, in the given question

The first term is [tex]a=\frac{1}{2}[/tex]

The common ratio [tex]r=\frac{3}{2}[/tex]

Now, fifth term is [tex]a_{5}=a_{1}r^{5-1}=a_{1}r^{4}[/tex]

[tex]=\frac{1}{2}\times \left ( \frac{3}{2} \right )^{4}=\frac{1}{2}\times \frac{81}{16}=\frac{81}{32}[/tex]

Sixth term [tex]a_{6}=a_{1}r^{6-1}=a_{1}r^{5}[/tex]

[tex]=\frac{1}{2}\times \left ( \frac{3}{2} \right )^{5}=\frac{1}{2}\times \frac{243}{32}=\frac{243}{64}[/tex]

.

.

.

nth term is [tex]a_{n}=a_{1}r^{n-1}[/tex].